2015
DOI: 10.1136/sextrans-2014-051732
|View full text |Cite
|
Sign up to set email alerts
|

Targeting core groups for gonorrhoea control: feasibility and impact

Abstract: Worldwide functional Gonorrhoea Antimicrobial Surveillance Program, better screening and better treatment programmes are needed. Prevention through condom promotion aimed at core groups remains essential. More specific treatment guidance for low-income and middle-income countries without resistance data is required in the meantime to achieve a better use of antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…28 Studies of gonorrhoea have also shown localised clustering of cases, and the impact of geotargeted interventions to these areas. 6 However, empirical and modelling studies of other infectious diseases identified several factors affecting the potential effects of targeting hotspots, including the connectivity between hotspots and other areas, the reproductive numbers of infections in each location, and the timing of interventions. 1,3 HIV spreads between geographical areas through two mechanisms: when infection is spread between sexual partners from different communities of residence, and when infection is spread by migration of people infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Studies of gonorrhoea have also shown localised clustering of cases, and the impact of geotargeted interventions to these areas. 6 However, empirical and modelling studies of other infectious diseases identified several factors affecting the potential effects of targeting hotspots, including the connectivity between hotspots and other areas, the reproductive numbers of infections in each location, and the timing of interventions. 1,3 HIV spreads between geographical areas through two mechanisms: when infection is spread between sexual partners from different communities of residence, and when infection is spread by migration of people infected with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…1 Targeting core groups has been used in the control of sexually transmitted infections for decades, 5 for example gonorrhoea, in which geo-targeted approaches to high-burden areas have proved effective. 6 With respect to HIV, the President's Emergency Plan for AIDS Relief, the Global Fund, WHO, and UNAIDS among others have advocated geographical targeting of HIV control interventions to hotspots. 7,8 These recommendations include calls for HIV elimination in the USA, based on targeting of geo graphical hotspots to "disrupt the kinetics of HIV spread".…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the observed variation could impact the ideal combination of local HIV interventions (Nosyk et al, 2020). These findings also suggest that efforts to target high-risk individuals to prevent STIs (Giguère & Alary, 2015) may not yield the expected prevention benefits if these individuals do not maintain a consistent level of risk. However, to the extent that these temporary periods of high-risk can be understood and predicted, tailored interventions could be implemented for individuals during these periods.…”
Section: Discussionmentioning
confidence: 99%
“…21 Accordingly, the observed variation could impact the ideal combination of local HIV interventions. 45 These findings also suggest efforts to target high-risk individuals to prevent STIs 46 may not yield the expected prevention benefits if these individuals do not maintain consistent levels of risk. However, to the extent that these temporary periods of high-risk can be understood and predicted, tailored interventions could be implemented during these periods.…”
Section: Discussionmentioning
confidence: 99%